The Effects of Reading Activity on Episodic Memory in Elderly - Ummu Ma’rifatul Afifah; Nanang Wiyono; Yunia Hastami; Siti Munawaroh (Berkala Kedokteran, 2021)
Abstract: The aging process is a natural event that cannot be avoided. Especially in the elderly, this is accompanied by a decrease in episodic memory function, which can reduce the quality of life. Therefore, efforts are needed to maintain cognitive function in elderly, one of which is through routine cognitive activities such as reading which can affect memory function in elderly through neuroplasticity. This study aims to determine the effect of reading activity on episodic memory function in the elderly. This research is a quasi-experimental study with a pre-test post-test control group design method. The total research subject were 30 people in Desa Demangan Siman, Kabupaten Ponorogo and Kelurahan Ngadirejo, Kota Kediri, with a sample technique using random purposive sampling. The research subjects were then divided into 3 groups with random allocation techniques using microsoft excel. Group 1 was the control group, group 2 was the 15-minute reading aloud intervention group, and group 3 was the 30-minute reading aloud intervention group. The results of the Dependent T-test showed that there was a significant difference in mean scores between the pre-test and post-test scores in group 2 (p = 0.000) and group 3 (p = 0.000), but not significant in group 1 (p = 0.111). The One Way ANOVA test results showed a significant difference in post-test scores in the three groups (p = 0.043), and the Post-hoc LSD test found a significant difference in scores between the post-test scores in group 1 with group 2 (p = 0.025) and group 1 with group 3 (p = 0.034), but there was no significant difference between the post-test scores in group 2 with group 3 (p = 0.883). It can be concluded, there is a significant effect between the duration of reading activity and episodic memory function in the elderly. Keywords: aging, elderly, episodic memory, reading, neuroplasticity.